Substituted spirooxindole derivatives as potent anticancer agents through inhibition of phosphodiesterase 1. Issue 26 (17th April 2018) - Barakat, Assem; Islam, Mohammad Shahidul; Ghawas, Hussien Mansur; Al-Majid, Abdullah Mohammed; El-Senduny, Fardous F.; Badria, Farid A.; Elshaier, Yaseen A. M. M.; Ghabbour, Hazem A.
Abstract : Spirooxindole is a promising chemo therapeutic agent. Possible targets include cancers of the liver, prostate, lung, stomach, colon, and breast. Abstract : Spirooxindole is a promising chemo therapeutic agent. Possible targets include cancers of the liver, prostate, lung, stomach, colon, and breast. Here, we demonstrate a one-pot three-component reaction via a [3 + 2] cycloaddition/ring contraction sequence of a dipolarophile (activated alkene) with in situ -generated azomethine ylide (1, 3-dipoles) without the use of any catalyst. The reaction provides efficient access to synthetically useful and biologically important spirooxindoles in high yield (69–94%) with high diastereoselectivity. The synthesized compounds were subjected to cytotoxicity evaluation using colorectal cancer (HCT-116), hepatocellular carcinoma (HepG2), and prostate cancer (PC-3) cells. Compounds4i, 4j, and4k showed potent cytotoxic activity and high selectivity against HCT-116 cells when compared to cisplatin. Meanwhile compound4d retained high cytotoxic activity and selectivity against HepG2 and PC-3 cells in comparison to cisplatin. The mechanism of compound4d was further studied using phosphodiesterase 1 enzyme and showed 74.2% inhibitory activity. A possible binding mode for compound4d to PDE-1 was investigated by molecular modeling using OpenEye software. Pose predictions for the active compounds were demonstrated by ROCS alignments. Compound4d has a special geometry and differs from other active compounds.